Концептуальні основи формування венчурних структур та їх моніторинг - Терлецька, В. О.; Terletska, V. O. (Видавництво Львівської політехніки, 2023)
У статті досліджено й обґрунтовано концептуальну модель формування венчурної структури, яка, на відміну від наявних, ґрунтується на основних системоутворювальних вимогах, охоплює технологію формування венчурних структур, що спирається на принципи формування; мету, місію і цілі формування; програму та напрями розвитку; способи інвестування активів; форми організації венчурного підприємництва; функції; типи венчурних структур; види венчурного підприємництва; постулати діяльності; інструменти венчурної діяльності; моделі формування, а також джерела формування венчурного капіталу; суб’єкти венчурної діяльності; напрями інвестування та структуру інвестицій; об’єкти венчурної діяльності, що відображає особливості функціонування венчурних структур і забезпечує досягнення інтересів сторін взаємодії. Досліджено джерела формування венчурного капіталу, подано суб’єктів венчурної діяльності, напрями інвестування та структуру інвестицій, а також об’єкти венчурної діяльності.

Venture entrepreneurship guarantees high profitability for investors, has proven the effectiveness of the venture investment institute in developed countries as one of the effective tools for implementing an innovative growth model. The goals of the article are to create a conceptual model of the formation of a venture structure, which, unlike the existing ones, is based on the main system-forming requirements, covers the technology of formation of venture structures, which is based on the principles of formation; the purpose, mission and goals of the formation; program and directions of development; ways of investing assets; forms of organization of venture entrepreneurship; functions; types of venture structures; types of venture entrepreneurship; postulates of activity; tools of venture activity; models of formation, as well as sources of formation of venture capital; subjects of venture activity; investment directions and investment structure; objects of venture activity, which reflects the peculiarities of the functioning of venture structures and ensures the achievement of the interests of the parties of interaction. Given the peculiarities of the activities of venture structures, the conceptual model of the formation of venture structures takes into account the technology of the formation of venture structures, as a purposeful sequence of actions that includes methods and means of management and allows to influence the subject of research and includes a complete toolkit according to the principles of the formation of venture structures; principles of formation of venture structures; purpose, mission and goals of formation of venture structures; plan, program and development directions of venture structures; ways of investing funds by venture structures; forms of organization of venture entrepreneurship; functions of venture structures; types of venture structures; types of venture entrepreneurship; postulates of activity of venture structures; tools of venture activity and models of formation of venture structures; and also takes into account the sources of formation of venture capital, subjects of venture activity, directions of investment and the structure of investments and objects of venture activity. The structure of the organization of venture activity is multifaceted in terms of types of venture activity, and its basis is the interaction of economic entities from filling the bank of innovative ideas to the commercialization of a newly created business and other types of activity. The article researches and substantiates the conceptual model of the formation of a venture structure, which, unlike the existing ones, is based on the main system-forming requirements, covers the technology of formation of a venture structure, which is based on the principles of formation; the purpose, mission and goals of the formation; program and directions of development; ways of investing assets; forms of organization of venture entrepreneurship; functions; types of venture structures; types of venture entrepreneurship; postulates of activity; tools of venture activity; models of formation, as well as sources of formation of venture capital; subjects of venture activity; investment directions and investment structure; objects of venture activity, which reflects the peculiarities of the functioning of venture structures and ensures the achievement of the interests of the parties of interaction. The sources of formation of venture capital are studied, the subjects of venture activity, directions of investment and the structure of investments, as well as objects of venture activity are presented.
Conceptual basis of formation of venture structures
Keywords: венчурна структура; формування венчурної структури; інноваційні проєкти; venture structures; venture business; innovative projects; 334.7